Design and Performance Analysis of Portable LTE-R Test Equipment - BAI Guoyan (机车电传动)
According to the problem of large volume, poor operability and portability, requiring vehicle power supply of the LTE-R specific testing instrument, a portable LTE-R testing equipment using software radio technology was designed, which realized RF signal pre-processing, data acquisition, transmission, storage and display with the mixer circuit, RF switch circuit, high-speed ADC sampling circuit and ARM control and display system. Combining software radio technology and embedded system technology, the portable LTE-R testing equipment finally achieved the effect of the size of the portable tablet computer with operability and good portability. The LTE-R coverage testing analysis and SINR testing analysis of Shuo-Huang line showed that the portable LTE-R testing equipment met the demand of actual measurement, and the efficiency in the field of construction measurement could be effectively improved.